1998
DOI: 10.1063/1.476809
|View full text |Cite
|
Sign up to set email alerts
|

The metastable T−P phase diagram and anomalous thermodynamic properties of supercooled water

Abstract: The metastable T−P phase diagram and the anomalies of the thermodynamic properties of supercooled water are calculated on the basis of a two-level thermodynamic model. Water is considered as a mixture of two components which differ in atomic configurations and correspond to low-density amorphous (lda) and high-density amorphous (hda) ice. The expression for the Gibbs potential of water is written in the form which is analogous to that of usual regular binary solutions. But this model considers the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 37 publications
4
74
0
Order By: Relevance
“…Finally, it should be also mention that we have found that the metastable phase diagrams of the spin-3 2 Ising BEG model for K/Jp0, which has served as a paradigm for a large number of physically important phenomena, always exists at the low temperatures that are consistent with experimental and theoretical works on some alloys [39][40][41], semiconductors [42][43][44][45], polymers [46], water [47] and the ternary system [47]. Moreover, the spin-1 BEG model have been used to calculate the metastable phase diagrams of some real systems such as Cu-Al-Mn shape-memory alloys [41], semiconductor alloys [44,45] and the ternary system [48] and the unstable continuation of the second-order phase transition line in (A III B V ) 1Àx C IV 2 x -semiconductor alloys [45].…”
Section: Discussionsupporting
confidence: 52%
“…Finally, it should be also mention that we have found that the metastable phase diagrams of the spin-3 2 Ising BEG model for K/Jp0, which has served as a paradigm for a large number of physically important phenomena, always exists at the low temperatures that are consistent with experimental and theoretical works on some alloys [39][40][41], semiconductors [42][43][44][45], polymers [46], water [47] and the ternary system [47]. Moreover, the spin-1 BEG model have been used to calculate the metastable phase diagrams of some real systems such as Cu-Al-Mn shape-memory alloys [41], semiconductor alloys [44,45] and the ternary system [48] and the unstable continuation of the second-order phase transition line in (A III B V ) 1Àx C IV 2 x -semiconductor alloys [45].…”
Section: Discussionsupporting
confidence: 52%
“…[5]. It should be also mention that we have found that the metastable phase diagrams of the BEG model for K=Jp0, which has served as a paradigm for a large number of physically important phenomena, always exists at the low temperatures that are consistent with experimental and theoretical works on some alloys [41][42][43], semiconductors [44,45] polymers [46], water [47] and the ternary system [48]. On the other hand, unstable phase transitions occur at low temperatures, which is also consistent with the work on ðA II B V Þ IÀX C IV 2X semiconductors alloys [49].…”
Section: Discussionsupporting
confidence: 58%
“…The hydrogen bond network in HDA is deformed strongly in a manner analogous to that found in water at high temperatures, whereas the pair correlation function of LDA is closer to that of supercooled water [183]. At ambient conditions, water was suggested to be a mixture of HDA-like and LDAlike states in an approximate proportion 2:3 [184][185][186].…”
Section: B Structural Informationmentioning
confidence: 92%